2021
DOI: 10.1097/md.0000000000026071
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between peripheral neuropathy and cognitive performance in the elderly population

Abstract: There are only a few studies that have shown an association of peripheral neuropathy with cognitive impairment in elderly individuals. Therefore, we investigated the relationship between cognitive performance and peripheral neuropathy. From the database of the National Health and Nutrition Examination Survey (NHANES, 1999–2002), each participant completed a household interview, physical performance test, questionnaire regarding personal health, and Digit Symbol Substitution Test (DSST) to evaluate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…These results are congruent with previous studies that have found that dementia, mental health disorders, chronic pain, and sleep disorders were common in individuals following a stroke (29)(30)(31)(32)(33). In addition, neuropathy has been previously linked to chronic pain, various mental health disorders, sleep disorders, lower cognitive performance, and inhalant addiction (34)(35)(36)(37)(38)(39). Given that individuals with these complications have a higher risk for these neuropsychological outcomes, preventing or improving complications such as neuropathy or stroke in individuals with diabetes may simultaneously improve their neuropsychological prospects, and therefore, should be the focus of future studies.…”
Section: Discussionsupporting
confidence: 91%
“…These results are congruent with previous studies that have found that dementia, mental health disorders, chronic pain, and sleep disorders were common in individuals following a stroke (29)(30)(31)(32)(33). In addition, neuropathy has been previously linked to chronic pain, various mental health disorders, sleep disorders, lower cognitive performance, and inhalant addiction (34)(35)(36)(37)(38)(39). Given that individuals with these complications have a higher risk for these neuropsychological outcomes, preventing or improving complications such as neuropathy or stroke in individuals with diabetes may simultaneously improve their neuropsychological prospects, and therefore, should be the focus of future studies.…”
Section: Discussionsupporting
confidence: 91%
“…The outcomes obtained in this study may be particularly useful for the development of rehabilitation programs aimed at improving both motor and cognitive skills in children with upper limb motor disorders. Furthermore, these findings confirm the affectation of the central nervous system in this clinical population, as previously suggested in recent studies, thus demonstrating the causal relationship between peripheral motor dysfunction and cognitive impairment [ 18 ]. From our point of view, the evaluation of children with motor impairment is often limited to their motor dysfunction, leaving their cognitive development neglected.…”
Section: Introductionsupporting
confidence: 90%
“…The aging process is a stage of the life cycle. In some cases, there are significant differences between individuals in the physical and cognitive state of the elderly [ 3 ], which leads to the loss of cognitive and physical abilities. Life satisfaction and physical activity are two key aspects of healthy aging [ 4 ].…”
Section: Introductionmentioning
confidence: 99%